Hubungan Karakteristik Individu dengan Kinerja Petugas Rekam Medis di Puskesmas Wilayah Kota Mataram - Rizal Pratama Adi Putra; Sismulyanto Sismulyanto; Agus Supinganto; Menap Menap; Sastrawan Sastrawan; Suardi Suardi; Uswatun Hasanah; Musparlin Halid (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Efforts to improve the performance of healthcare workers at Community Health Centers are crucial due to various aspects related to improving healthcare services. This study aimed to determine the relationship between individual characteristics and the performance of medical recorders at Community Health Centers in the Mataram City area. The research used a cross-sectional design with a sample size of 43 people. Bivariate analysis was used with a confidence level of 95% and a p-value <0.05. The study showed that there was no significant relationship between gender (p=0.737) and the performance of medical record officers. On the other hand, there were a relationship between educational background and performance with p=0.036, length of service and performance with p=0.036, age and performance with p=0.006. Additionally, employment status and performance with p=0.001, and training and performance with p=0.019. Therefore, individual characteristics such as educational qualifications, length of service, age, employment status, and training play an important role in improving the performance of medical record officers at Community Health Centers in the Mataram area. Healthcare service organizations need to optimize workforce management strategies and improve the quality of medical record management.